The urokinase gene knockout effects on growth factor dynamics in mice with melanoma, developing on the background of chronic neurogenic pain - E. M. Frantsiyants; I. V. Kaplieva; E. I. Surikova; I. V. Neskubina; V. A. Bandovkina; L. K. Trepitaki; N. D. Cheryarina; L. A. Nemashkalova; N. S. Lesovaya (Исследования и практика в медицине, 2019)
Purpose of the study. Studying the dynamics of growth factors (GF) in urokinase (uPA)-deficient mice with chronic neurogenic pain (CNP) and B16/F10 melanoma.Materials and methods. Levels of VEGFA, VEGFC, sVEGFRl, sVEGFR3, IGF1, IGF2, TGFp1 and FGF21 were determined by ELISA in tumors, perifocal tissues (PT) and the skin of male and female С57 BL/6 mice (with a normal genome, n = 75) and C57BL/6-Plautm1.1BugThisPlauGFDhu/GFDhu mice (uPA-deficient animals, n = 46) at 3nd week of the carcinogenesis and CNP.Results. The skin of intact uPA-deficient mice demonstrated higher GF levels than in C57BL/6 mice, but VEGF-А and TGF-p1 in males (unlike females) were 4.4 and 5 times lower than in C57BL/6 males. This changes were generally similar in the skin of C57BL/6 mice with CNP. uPA-deficient females showed elevated GF in PT, especially VEGF-А and IGF1 — by 21.5 and 8.1 times, respectively in simultaneously CNP and growth of the melanoma. uPA gene-knockout males had similar changes in GF, although less marked. The levels of all studied GF in tumor tissue were lower than levels in PT in both males and females, except for VEGFA in males — 5.6 times higher in tumor tissue. Changes in PT of C57BL/6 mice were similar: maximally increased levels of all GF, especially VEGF, IGF and TGF-p1 — in females on average by 6.2, 15.9 and 5.5 times, respectively, in males by 9.4, 5.9 and 6.7 times, respectively, compared to the skin levels. While the absolute values of GF concentrations and the intensity of changes were higher than in uPA-deficient mice.Conclusion. In general, skin levels of GF in intact uPA-deficient mice were similar to the levels in mice without uPA-deficient with CNP. The GF dynamics was analogous in mice of both lines at simultaneously CNP and growth of the melanoma, but the intensity of changes in mice without uPA-deficient was significantly higher implying a synergic effect of CNP and paracrine influence of melanoma on the GF levels.